A modified current collector and its preparation method and application

By coating the graphene coating on the surface of the aluminum foil current collector of the lithium battery and embedded meltblown fibers, the problem of poor bonding fastness of the aluminum foil current collector in the prior art is solved, and higher conductivity and heat dissipation performance are achieved, which extends the cycle life of the lithium battery and reduces the preparation cost.

CN119208619BActive Publication Date: 2025-04-01CTRON ADVANCED MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411738834.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-01
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In existing lithium batteries, the carbon material coating of aluminum foil current collector is not fast enough to bond with aluminum foil, which easily deforms during battery processing and causes the coating to fall off, resulting in a high charging and discharge temperature of lithium batteries and insufficient cycle life.

Method used

The modified current collector is used, including a graphene coating coated on the surface of the aluminum foil. The graphene coating is embedded with meltblown fibers. The meltblown fiber is made of polyaniline-carbon nanotube composite material. A three-dimensional mesh-like fiber layer is prepared on the surface of the aluminum foil by meltblown wire spraying technology, and the graphene slurry is uniformly coated on the fiber layer. Then, the modified current collector is dried in a vacuum drying box to obtain.

Benefits of technology

The bonding fastness between the carbon coating and aluminum foil is improved, the strength and crack resistance of the coating are enhanced, the coating is avoided, the charging and discharge temperature of the lithium battery is reduced, the recycling life of the battery is improved, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208619B_ABST
    Figure CN119208619B_ABST
Patent Text Reader

Abstract

The present application discloses a modified current collector and its preparation method and application. On the one hand, the present application provides a modified current collector, including an aluminum foil, the surface of the aluminum foil is coated with a graphene coating, and the graphene coating is provided with a melt-blown fiber; the graphene coating is prepared by curing a graphene slurry, and the components of the graphene slurry include a PVDF emulsion modified by methacrylate grafting, graphene and a solvent; the melt-blown fiber is a three-dimensional mesh structure, and is prepared using a polyaniline-carbon nanotube composite material. On the other hand, the present application also provides a preparation method and application of the above-mentioned modified current collector. The present application has a low preparation cost, the carbon material coating has a good bonding strength with the aluminum foil, and the coating is not easy to fall off. The application of lithium batteries can effectively reduce the battery charging and discharging temperature, and can effectively improve the battery cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a modified current collector and a preparation method and application thereof. Background Art

[0002] With the development of the electronic digital industry and the new energy vehicle industry, battery technology has been increasingly valued. Among them, lithium batteries with high energy density are widely used in mobile phones, computers, automobiles and other fields. Lithium batteries are composed of electrodes, diaphragms, electrolytes, tabs and shells. Electrodes are usually composed of positive / negative active materials and current collectors. The function of current collectors is to collect current and carry positive / negative active materials. Since the working principle of lithium batteries is to realize charging and discharging by the movement of lithium ions between the positive and negative electrodes, the current collector, as a carrier of active materials, has a great influence on the internal resistance and cycle performance of lithium batteries.

[0003] Based on factors such as cost, light weight and conductivity, aluminum foil current collectors account for a large proportion in current lithium batteries. Most of the existing aluminum foil current collectors use carbon-coated aluminum foil, which uses aluminum foil as the main body and is coated with a coating containing conductive carbon black or carbon-coated particles on the surface. Compared with traditional technologies, adding carbon material coating can not only effectively improve the conductivity of lithium batteries, but also effectively protect the aluminum foil from being corroded by electrolyte.

[0004] In the current prior art, the preparation of carbon-coated aluminum foil is mostly to mix carbon materials (such as conductive carbon black, graphene, etc.) with binders and solvents to make a mixed slurry in which the carbon materials are evenly dispersed, and then coated on the surface of the aluminum foil. After drying and curing, the aluminum foil with a carbon material layer coated on the surface can be obtained. Among them, the binder usually uses an aqueous or oily binder, and the aqueous binder is mostly an acrylic binder, and the oily binder usually uses a polyvinylidene fluoride binder. For example, the Chinese invention patent with the publication number CN111180741A and the invention name of the carbon-coated current collector coated with three-dimensional graphene powder and its preparation method uses the above method to prepare carbon-coated aluminum foil, using graphene as the carbon material, and the binder uses the existing aqueous or oily binder. Most of the carbon-coated aluminum foils in the prior art have problems such as poor bonding strength between the carbon material coating and the aluminum foil, and the coating is easily detached due to deformation during battery processing; as a result, after being applied to lithium batteries, the battery charging and discharging temperature is relatively high, and the cycle life is relatively insufficient. Summary of the invention

[0005] In order to solve at least one of the above technical problems, a carbon-coated aluminum foil current collector with low preparation cost, better bonding strength between the carbon material coating and the aluminum foil, and the coating that is not easy to fall off is developed. The present application provides a modified current collector and its preparation method and application.

[0006] On the one hand, the present application provides a modified current collector, including an aluminum foil, the surface of which is coated with a graphene coating, and melt-blown fibers are arranged in the graphene coating; the graphene coating is prepared by curing a graphene slurry, and the components of the graphene slurry include a PVDF emulsion modified by methacrylate grafting, graphene and a solvent; the melt-blown fibers are a three-dimensional network structure and are prepared using a polyaniline-carbon nanotube composite material.

[0007] Optionally, the thickness of the graphene coating is 1-30 μm.

[0008] Optionally, in the melt-blown fibers, the mass fraction of carbon nanotubes is not less than 10%.

[0009] Preferably, in the melt-blown fibers, the mass fraction of carbon nanotubes is 14-18%.

[0010] On the other hand, the present application provides a method for preparing the modified current collector, comprising the following steps:

[0011] S1. preparing a graphene slurry to prepare a polyaniline-carbon nanotube composite material;

[0012] S2, using a melt-blowing device, using the polyaniline-carbon nanotube composite material obtained in step S1 as a material, preparing melt-blown fibers with a three-dimensional network structure on the surface of the aluminum foil by melt-blowing, and obtaining an aluminum foil with a fiber layer;

[0013] S3, uniformly coating the graphene slurry obtained in step S1 on the surface of the aluminum foil with the fiber layer obtained in step S2, so that the slurry completely fills and covers the melt-blown fibers with a three-dimensional network structure, to obtain a current collector blank;

[0014] S4. Place the current collector blank obtained in step S2 in a vacuum drying oven, vacuum dry it to constant weight, and obtain a modified current collector after cooling.

[0015] Optionally, in step S1, the method for preparing the methacrylate graft-modified PVDF emulsion comprises the following steps:

[0016] S1-1, fully mixing PVDF emulsion and methacrylate in a mass ratio of 4-5:1 to prepare a mixed solution;

[0017] S1-2, the mixed solution obtained in step S1-1 was treated with Co 60 The γ-ray irradiation treatment has an irradiation dose of 8-12 kGy and an irradiation dose rate of 4-6 kGy / h to obtain a methacrylate grafted modified PVDF emulsion.

[0018] Optionally, in step S1, the mass fraction ratio of each component of the graphene slurry includes: 2-4% methacrylate grafted modified PVDF emulsion, 12-16% graphene, 0.2-1% dispersant, 0.4-0.6% curing agent, and the rest is solvent.

[0019] Optionally, the dispersant is polyvinyl pyrrolidone and the solvent is N-methyl pyrrolidone.

[0020] Optionally, in step S1, the method for preparing the polyaniline-carbon nanotube composite material comprises the following steps:

[0021] S1-3, accurately calculating the proportion according to the mass fraction requirement of carbon nanotubes in the polyaniline-carbon nanotube composite material, and then accurately weighing the aniline monomer and the carbon nanotubes;

[0022] S1-4, weighing the aniline monomer and the carbon nanotubes in step S1-3, adding them to deionized water, and performing ultrasonic dispersion treatment to obtain a dispersed mixed solution;

[0023] S1-5, adding concentrated hydrochloric acid to the dispersed mixed solution obtained in step S1-4, stirring and reacting for more than 120 minutes, filtering out the solid matter by suction, and washing to obtain a polyaniline-carbon nanotube composite material.

[0024] Optionally, in step S4, the drying temperature is controlled at 80-85°C.

[0025] In a third aspect, the present application provides the application of the above-mentioned modified current collector in the field of lithium batteries.

[0026] In summary, the present invention includes at least one of the following beneficial technical effects:

[0027] 1. In the present application, methacrylate-grafted modified PVDF emulsion, graphene and solvent are used as main raw materials to prepare a slurry to prepare a carbon coating for an aluminum foil current collector, which has excellent thermal conductivity and electrical conductivity; and methacrylate-grafted modified PVDF emulsion is used as a binder, and has a better bonding effect with the metal aluminum foil, and the prepared coating is not easy to fall off.

[0028] 2. The present application uses polyaniline-carbon nanotube composite materials as raw materials and prepares melt-blown fibers by melt-blowing. The fibers have a three-dimensional network structure and are located within the carbon coating. The fibers can effectively improve the strength and crack resistance of the carbon coating and effectively prevent the carbon coating of the current collector from cracking during lithium battery processing. In addition to enhancing the strength of the carbon coating, the polyaniline-carbon nanotube composite materials themselves have good electrical conductivity and therefore will not reduce the overall electrical conductivity of the carbon coating.

[0029] 3. The raw materials used in this application are easy to obtain, the overall preparation method is relatively simple, the preparation cost is low, and the quality of the obtained current collector is relatively excellent.

[0030] 4. The current collector of the present application is mainly made of aluminum foil, which is coated with a carbon coating of a specific material. The overall heat dissipation performance and conductivity are relatively excellent. When applied to lithium batteries, it can effectively reduce the battery charging and discharging temperature and effectively improve the battery's cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the structure of the modified current collector surface coating of the present application;

[0032] Figure 2 This is an electron microscope image of the surface coating of the current collector prepared in Example 1 of the present application;

[0033] Figure 3 This is an electron microscope image of the surface coating of the current collector prepared in Example 5 of the present application;

[0034] In the figure, 1. aluminum foil; 2. graphene coating; 3. melt-blown fiber. DETAILED DESCRIPTION

[0035] The present application is further described in detail below in conjunction with embodiments.

[0036] The present application provides a modified current collector, comprising an aluminum foil 1, wherein the surface of the aluminum foil 1 is coated with a graphene coating 2, wherein a melt-blown fiber 3 is arranged in the graphene coating 2. The graphene coating 2 is prepared by curing a graphene slurry, wherein the components of the graphene slurry include a methacrylate-grafted modified PVDF emulsion, graphene, and a solvent. The melt-blown fiber 3 is a three-dimensional network structure, and is prepared from a polyaniline-carbon nanotube composite material.

[0037] The preparation method of the modified current collector of the present application comprises the following steps:

[0038] S1. preparing a graphene slurry to prepare a polyaniline-carbon nanotube composite material;

[0039] S2, using a melt-blowing device, using the polyaniline-carbon nanotube composite material obtained in step S1 as a material, preparing melt-blown fibers 3 with a three-dimensional network structure on the surface of the aluminum foil 1 by melt-blowing, and obtaining an aluminum foil 1 with a fiber layer;

[0040] S3, the graphene slurry obtained in step S1 is evenly coated on the surface of the aluminum foil 1 with the fiber layer obtained in step S2, so that the slurry completely fills and covers the melt-blown fibers 3 with a three-dimensional network structure, to obtain a current collector blank;

[0041] S4. Place the current collector blank obtained in step S2 in a vacuum drying oven, vacuum dry it to constant weight, and obtain a modified current collector after cooling.

[0042] Preferably, in step S1, the mass fraction ratio of each component of the graphene slurry includes: 2-4% methacrylate grafted modified PVDF emulsion, 12-16% graphene, 0.2-1% dispersant, 0.4-0.6% curing agent, and the rest is solvent.

[0043] Carbon-coated aluminum foil current collector is currently the most widely used lithium battery current collector. Nearly 90% of commercially available lithium batteries use carbon-coated aluminum foil current collectors. Compared with pure aluminum foil or copper foil current collectors, carbon-coated aluminum foil current collectors used in lithium batteries can reduce the charge transfer resistance between the positive and negative electrodes and the internal resistance of the battery, weaken the internal polarization of the battery, and increase the diffusion rate of lithium ions in the material, thereby improving the battery's rate performance and cycle performance. In addition, after setting the external carbon coating, it can protect the aluminum foil and prevent the electrolyte from corroding the aluminum foil, thereby effectively increasing the service life of the current collector and thus increasing the cycle life of the battery.

[0044] The performance of the carbon-coated aluminum foil current collector depends entirely on the electrical conductivity, thermal conductivity, and adhesion strength of the carbon coating to the aluminum foil. The electrolyte of lithium batteries is highly corrosive. Based on the above technical requirements and the need for corrosion resistance, the carbon-coated aluminum foil is mainly coated with carbon materials. However, the carbon material itself does not have adhesion, so a binder needs to be added to ensure the adhesion of the coating. Based on corrosion resistance considerations, most of the existing technologies choose PVDF oily binders; some products using acrylic binders have effectively improved the adhesion of the coating, but the corrosion resistance is poor. In the existing technology, in order to enhance the strength of the coating, a small number of carbon-coated current collectors will mix fiber materials (such as polypropylene fibers, polyethylene fibers or natural fibers, etc.) into the coating, but the above fibers are not conductive, and thus have a certain impact on the overall conductivity and heat dissipation of the current collector.

[0045] The design of the present application uses methyl methacrylate grafted modified PVDF emulsion as a binder, which has both strong corrosion resistance and relatively good bonding performance; in addition, the melt-blown fiber added with polyaniline-carbon nanotube composite material effectively enhances the coating strength and crack resistance without affecting the conductivity and heat dissipation performance; therefore, the present application can effectively solve the various problems existing in the existing carbon-coated aluminum foil.

[0046] In order to further improve the adhesion strength of the coating, in the preparation method of the present application, in step S2, before the melt-blowing operation, the surface of the aluminum foil 1 needs to be micro-etched to form micro-pits with a size of 400-1200 nm on the surface. This can be done by existing photolithography or electron beam etching.

[0047] In addition, in order to effectively disperse graphene, in the preparation method of the present application, in step S1, the graphene slurry is prepared by the following steps:

[0048] Sa, mixing the formulated amount of graphene and dispersant, placing the mixture in the formulated amount of solvent to prepare a mixture;

[0049] Sb, subjecting the mixture obtained in step Sa to ultrasonic dispersion treatment for more than 30 min to obtain a graphene mixed solution;

[0050] Sc. Add the methacrylate graft-modified PVDF emulsion and the remaining components of the graphene slurry in the formula amount to the graphene mixed solution obtained in step Sb, stir and mix for more than 15 minutes, and then ultrasonically disperse for more than 30 minutes to obtain the graphene slurry.

[0051] The following are preparation examples and embodiments of the present application:

[0052] The raw materials used in the preparation examples and examples of this application are basically purchased from the market, and the graphene is produced by the applicant. The graphene particle size is 40-80nm. In the preparation examples and examples of this application, polyvinyl pyrrolidone is used as the dispersant of the graphene slurry, and N-methylpyrrolidone solution is used as the solvent. The aluminum foil used in the preparation examples, examples and comparative examples of this application is an aluminum foil with a thickness of 15μm.

[0053] In the preparation examples and embodiments of the present application, the preparation method of the methacrylate graft-modified PVDF emulsion comprises the following steps:

[0054] S1-1, fully mixing PVDF emulsion and methacrylate in a mass ratio of 4.5:1 to prepare a mixed solution;

[0055] S1-2, the mixed solution obtained in step S1-1 was treated with Co 60 The γ-ray irradiation treatment has an irradiation dose of 11 kGy and an irradiation dose rate of 5 kGy / h to obtain a methacrylate grafted modified PVDF emulsion.

[0056] The following is the preparation example of this application

[0057] Preparation Example 1

[0058] The mass fraction ratio of each component of the graphene slurry in this preparation example includes: 2% of methacrylate graft-modified PVDF emulsion, 12% of graphene, 0.2% of dispersant, 0.4% of curing agent, and the rest is solvent.

[0059] The method for preparing the graphene slurry comprises the following steps:

[0060] Sa, mixing the formulated amount of graphene and dispersant, placing the mixture in the formulated amount of solvent to prepare a mixture;

[0061] Sb, subjecting the mixture obtained in step Sa to ultrasonic dispersion treatment for 30 min to obtain a graphene mixed solution;

[0062] Sc. Add the formulated amount of methacrylate-grafted modified PVDF emulsion and the remaining components of the graphene slurry to the graphene mixed solution obtained in step Sb, stir and mix for 15 minutes, and then ultrasonically disperse for 30 minutes to obtain a graphene slurry.

[0063] Preparation Example 2

[0064] The mass fraction ratio of each component of the graphene slurry in this preparation example includes: 4% of methacrylate graft-modified PVDF emulsion, 16% of graphene, 1% of dispersant, 0.6% of curing agent, and the rest is solvent.

[0065] The configuration method of graphene slurry is the same as that of Preparation Example 1.

[0066] Preparation Example 3

[0067] The mass fraction ratio of each component of the graphene slurry in this preparation example includes: 2.8% of methacrylate grafted modified PVDF emulsion, 14% of graphene, 0.6% of dispersant, 0.5% of curing agent, and the rest is solvent.

[0068] The configuration method of graphene slurry is the same as that of Preparation Example 1.

[0069] Preparation Example 4

[0070] The preparation method of the polyaniline-carbon nanotube composite material of this preparation example comprises the following steps:

[0071] S1-3, according to the mass fraction of carbon nanotubes in the polyaniline-carbon nanotube composite material of 10%, accurately calculate the ratio, and then accurately weigh the aniline monomer and the carbon nanotubes;

[0072] S1-4, weighing the aniline monomer and carbon nanotubes in step S1-3, adding them to deionized water, and performing ultrasonic dispersion treatment for 30 minutes to obtain a dispersed mixed solution;

[0073] S1-5. Add concentrated hydrochloric acid to the dispersed mixed solution obtained in step S1-4, stir and react for 120 minutes, filter out the solid matter by suction, wash with acetone and air-dry to obtain a polyaniline-carbon nanotube composite material.

[0074] Preparation Example 5

[0075] The preparation method of the polyaniline-carbon nanotube composite material of this preparation example comprises the following steps:

[0076] S1-3, according to the mass fraction of carbon nanotubes in the polyaniline-carbon nanotube composite material of 14%, accurately calculate the ratio, and then accurately weigh the aniline monomer and the carbon nanotubes;

[0077] S1-4, weighing the aniline monomer and carbon nanotubes in step S1-3, adding them to deionized water, and performing ultrasonic dispersion treatment for 30 minutes to obtain a dispersed mixed solution;

[0078] S1-5. Add concentrated hydrochloric acid to the dispersed mixed solution obtained in step S1-4, stir and react for 120 minutes, filter out the solid matter by suction, wash with acetone and air-dry to obtain a polyaniline-carbon nanotube composite material.

[0079] Preparation Example 6

[0080] The preparation method of the polyaniline-carbon nanotube composite material of this preparation example comprises the following steps:

[0081] S1-3, according to the mass fraction of carbon nanotubes in the polyaniline-carbon nanotube composite material of 18%, accurately calculate the ratio, and then accurately weigh the aniline monomer and the carbon nanotubes;

[0082] S1-4, weighing the aniline monomer and carbon nanotubes in step S1-3, adding them to deionized water, and performing ultrasonic dispersion treatment for 30 minutes to obtain a dispersed mixed solution;

[0083] S1-5. Add concentrated hydrochloric acid to the dispersed mixed solution obtained in step S1-4, stir and react for 120 minutes, filter out the solid matter by suction, wash with acetone and air-dry to obtain a polyaniline-carbon nanotube composite material.

[0084] The following are examples of the present application: Example 1

[0085] The preparation method of the modified current collector of this embodiment comprises the following steps:

[0086] S1, selecting the graphene slurry of Preparation Example 1 and the polyaniline-carbon nanotube composite material of Preparation Example 4;

[0087] S2, using a melt-blowing device, using the polyaniline-carbon nanotube composite material obtained in step S1 as a material, preparing melt-blown fibers 3 with a three-dimensional network structure on the surface of the aluminum foil 1 by melt-blowing, and obtaining an aluminum foil 1 with a fiber layer;

[0088] S3, the graphene slurry obtained in step S1 is evenly coated on the surface of the aluminum foil 1 with the fiber layer obtained in step S2, with a coating thickness of 1 μm, so that the slurry completely fills and covers the melt-blown fibers with a three-dimensional network structure, to obtain a current collector blank;

[0089] S4. Place the current collector blank obtained in step S2 in a vacuum drying oven, vacuum dry it at 80° C. to a constant weight, and cool it naturally to obtain a modified current collector. Example 2

[0090] The difference between this embodiment and embodiment 1 is that in step S1, the graphene slurry of preparation example 2 is selected. Example 3

[0091] The difference between this embodiment and embodiment 1 is that in step S1, the graphene slurry of preparation example 3 is selected. Example 4

[0092] The difference between this embodiment and embodiment 3 is that in step S1, the polyaniline-carbon nanotube composite material of preparation example 5 is selected. Example 5

[0093] The difference between this embodiment and embodiment 3 is that in step S1, the polyaniline-carbon nanotube composite material of preparation example 6 is selected. Example 6

[0094] The difference between this embodiment and embodiment 5 is that in step S2, the surface of the aluminum foil 1 is first micro-etched by electron beam etching to etch micro-pits with a size of about 800 nm and a spacing of 1000 nm on the surface of the aluminum foil 1; and then the melt-blowing operation is performed. Example 7

[0095] The difference between this embodiment and embodiment 6 is that in step S3, the graphene slurry coating thickness is 15 μm. Example 8

[0096] The difference between this embodiment and embodiment 6 is that in step S3, the graphene slurry coating thickness is 30 μm.

[0097] Comparative Example 1

[0098] Example 1 of the Chinese invention patent with publication number CN111180741A and invention name carbon-coated current collector coated with three-dimensional graphene powder and preparation method thereof is used as comparative example 1 of the present application, and the coating thickness is 20 μm.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 7 is that the method for preparing the graphene slurry comprises the following steps: mixing the components of the formulated graphene slurry, and then stirring and mixing at a high speed of 1000 rpm for 60 minutes to obtain the graphene slurry.

[0101] Comparative Example 3

[0102] The difference between this comparative example and Example 7 is that a PVDF oily binder is used instead of the methacrylate graft-modified PVDF emulsion.

[0103] Comparative Example 4

[0104] The difference between this comparative example and Example 7 is that the melt-blown fiber 3 is not provided.

[0105] Comparative Example 5

[0106] The difference between this comparative example and Example 7 is that melt-blown fiber 3 is replaced by melt-blown polypropylene fiber.

[0107] Comparative Example 6

[0108] The difference between this comparative example and Example 7 is that conductive carbon black nanopowder is used instead of graphene.

[0109] Performance Testing

[0110] Relevant performance tests were performed on the current collectors of Examples 1 to 8 and Comparative Examples 1 to 6 of the present application.

[0111] Detection method:

[0112] The current collectors of Examples 1 to 8 and Comparative Examples 1 to 6 of the present application were used as positive current collectors to assemble lithium batteries, and then the performance of the lithium batteries was tested to test the 5C discharge temperature rise, 1000 charge and discharge cycle capacity retention rate, and positive electrode material peel strength of the lithium batteries. A pure aluminum foil current collector was used as a control example.

[0113] Among them, the 5C discharge temperature rise and the capacity retention rate of 1000 charge and discharge cycles are tested using the method described in GB / T 36276-2018; the peeling strength of the positive electrode material is tested using a DBL-01 electronic peeling tester.

[0114] The test results are shown in Table 1 below.

[0115] Table 1 Test results of Examples 1 to 8 and Comparative Examples 1 to 6

[0116] Discharge temperature rise (℃) Capacity retention rate (%) Peel strength (N / m) Example 1 14.6 96.4 124.4 Example 2 14.8 96.2 123.6 Example 3 14.5 96.5 124.9 Example 4 14.3 96.7 125.2 Example 5 14.2 96.8 125.3 Example 6 14.3 97.1 130.6 Example 7 13.6 97.4 137.1 Example 8 13.8 97.2 136.9 Comparative Example 1 16.1 95.4 101.2 Comparative Example 2 18.7 92.3 92.1 Comparative Example 3 18.4 93.6 86.2 Comparative Example 4 16.7 94.2 95.4 Comparative Example 5 17.2 93.3 90.6 Comparative Example 6 16.4 94.6 94.8 Comparison Example 38.8 72.6 38.2

[0117] It can be seen from the data in Table 1 that the current collectors of Examples 1 to 8 of the present application, compared with the current collectors of Examples 1 to 6 and the control example, are used in the assembly of lithium batteries, and the discharge temperature rise is significantly reduced, the peel strength of the positive electrode material is significantly improved, and the capacity retention rate after 1000 charge and discharge cycles is significantly improved. It can be seen that after using a specific binder and a specific modified fiber, the bonding strength of the carbon coating of the current collector is significantly improved, and the conductivity and heat dissipation performance of the current collector are also more excellent.

[0118] From the data in Table 1, it can be seen from the data comparison of the current collectors of Examples 1 to 8 that the thickness of the carbon coating has an impact on the performance of the current collector. If it is too thin, the graphene slurry will be unevenly distributed and the performance will be reduced. If it is too thick, it will not have a positive effect on the performance, but will increase the thickness and weight of the battery, and the cost will also increase accordingly. Therefore, it is appropriate to control the thickness to about 1 to 30 μm, preferably 12 to 18 μm.

[0119] From the data comparison of the current collectors of Examples 1 to 8 in Table 1, it can be seen that the higher the carbon nanotube content in the polyaniline-carbon nanotube composite material, the better the performance; however, if the carbon nanotube content of the polyaniline-carbon nanotube composite material exceeds 18%, it will affect the strength of the fiber, so it is appropriate to control the carbon nanotube content within the range of 14 to 18%.

[0120] The current collectors of Example 1, Example 5 and Comparative Example 2 of the present application were tested by surface electron microscopy. The test results of Example 1 and Example 5 are as follows: Figure 2 and Figure 3 It can be seen from the data in Table 1 and the electron microscope test results that after the graphene slurry of the present application adopts a specific configuration method, the graphene can be dispersed more evenly, thereby effectively improving the performance of the current collector.

[0121] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A modified current collector, comprising an aluminum foil (1), characterized in that: The surface of the aluminum foil (1) is coated with a graphene coating (2), and melt-blown fibers (3) are arranged in the graphene coating (2); the graphene coating (2) is obtained by curing a graphene slurry, and the components of the graphene slurry include a methyl acrylate grafted modified PVDF emulsion, graphene, and a solvent; the melt-blown fibers (3) are three-dimensional network structures and are made of a polyaniline-carbon nanotube composite material; To prepare the graphene slurry, the following steps are adopted: Sa, mixing the formulated amount of graphene and dispersant, placing the mixture in the formulated amount of solvent to prepare a mixture; Sb, subjecting the mixture obtained in step Sa to ultrasonic dispersion treatment for more than 30 min to obtain a graphene mixed solution; Sc, adding the methacrylate graft-modified PVDF emulsion and the remaining components of the graphene slurry to the graphene mixed solution obtained in step Sb, stirring and mixing for more than 15 minutes, and then ultrasonically dispersing for more than 30 minutes to obtain a graphene slurry; The method for preparing the modified current collector comprises the following steps: S1, preparing a graphene slurry to prepare a polyaniline-carbon nanotube composite material; S2, using a melt-blowing device, using the polyaniline-carbon nanotube composite material obtained in step S1 as a material, and preparing melt-blown fibers (3) with a three-dimensional network structure on the surface of the aluminum foil (1) by melt-blowing, thereby obtaining an aluminum foil (1) with a fiber layer; S3, the graphene slurry obtained in step S1 is evenly coated on the surface of the aluminum foil (1) with the fiber layer obtained in step S2, so that the slurry completely fills and covers the melt-blown fibers (3) with a three-dimensional network structure, thereby obtaining a current collector blank; S4. Place the current collector blank obtained in step S3 in a vacuum drying oven, vacuum dry it to constant weight, and obtain a modified current collector after cooling.

2. The modified current collector according to claim 1, characterized in that: The graphene coating (2) has a thickness of 1 to 30 μm.

3. The modified current collector according to claim 1, characterized in that: In the melt-blown fibers (3), the mass fraction of carbon nanotubes is not less than 10%.

4. A method for preparing the modified current collector according to claim 1, characterized in that: The following steps are involved: S1, preparing a graphene slurry to prepare a polyaniline-carbon nanotube composite material; S2, using a melt-blowing device, using the polyaniline-carbon nanotube composite material obtained in step S1 as a material, and preparing melt-blown fibers (3) with a three-dimensional network structure on the surface of the aluminum foil (1) by melt-blowing, thereby obtaining an aluminum foil (1) with a fiber layer; S3, the graphene slurry obtained in step S1 is evenly coated on the surface of the aluminum foil (1) with the fiber layer obtained in step S2, so that the slurry completely fills and covers the melt-blown fibers (3) with a three-dimensional network structure, thereby obtaining a current collector blank; S4. Place the current collector blank obtained in step S3 in a vacuum drying oven, vacuum dry it to constant weight, and obtain a modified current collector after cooling.

5. The method for preparing the modified current collector according to claim 4, characterized in that: In step S1, the method for preparing the methacrylate graft-modified PVDF emulsion comprises the following steps: S1-1, fully mixing PVDF emulsion and methacrylate in a mass ratio of 4-5:1 to prepare a mixed solution; S1-2, the mixed solution obtained in step S1-1 was treated with Co 60 The γ-ray irradiation treatment has an irradiation dose of 8-12 kGy and an irradiation dose rate of 4-6 kGy / h to obtain a methacrylate grafted modified PVDF emulsion.

6. The method for preparing the modified current collector according to claim 4, characterized in that: In the step S1, the mass fraction ratio of each component of the graphene slurry includes: 2-4% methacrylate grafted modified PVDF emulsion, 12-16% graphene, 0.2-1% dispersant, 0.4-0.6% curing agent, and the rest is solvent.

7. The method for preparing the modified current collector according to claim 6, characterized in that: The dispersant is polyvinyl pyrrolidone, and the solvent is N-methyl pyrrolidone.

8. The method for preparing the modified current collector according to claim 4, characterized in that: In step S4, the drying temperature is controlled at 80-85°C.

9. Use of the modified current collector according to any one of claims 1 to 3 in the field of lithium batteries.

Citation Information

Patent Citations

  • Carbon-coated current collector coated with three-dimensional graphene powder and preparation method of carbon-coated current collector

    CN111180741A

  • Short fiber polyaniline and application thereof in water-based heavy anti-corrosion coating

    CN114316259A

  • Modified PVDF material, preparation method thereof, modified PVDF ultrafiltration membrane and application of modified PVDF ultrafiltration membrane

    CN116617876A

  • Electrode and preparation method and application thereof

    CN118867117A

  • Binders for electrodes and their production method

    CN1212076A